2013
DOI: 10.1371/journal.pone.0071546
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Healthcare Preferences among Gay and Bisexual Men: A Qualitative Study in San Francisco, California

Abstract: BackgroundResearch on gay and other men who have sex with men's (G/MSM) preferences for sexual healthcare services focuses largely on HIV testing and to some extent on sexually transmitted infections (STI). This research illustrates the frequency and location of where G/MSM interface with the healthcare system, but it does not speak to why men seek care in those locations. As HIV and STI prevention strategies evolve, evidence about G/MSM's motivations and decision-making can inform future plans to optimize mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 51 publications
2
33
1
Order By: Relevance
“…Consistent with previous studies on preferences for alternative testing approaches,9 the main findings of this study suggest that rapid testing and/or testing in non-healthcare settings are highly preferred by GMSM, particularly those who engaged in risky sexual behaviours (UAIC) and/or having a busy lifestyle (employed full time and in professional or managerial occupations, making it difficult to take time off work) and hence a desire for testing convenience and rapidly accessible results. Three quarters of the participants expressed preferences for rapid testing over the current standard-of-care and more than half preferred to be tested in non-healthcare settings.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous studies on preferences for alternative testing approaches,9 the main findings of this study suggest that rapid testing and/or testing in non-healthcare settings are highly preferred by GMSM, particularly those who engaged in risky sexual behaviours (UAIC) and/or having a busy lifestyle (employed full time and in professional or managerial occupations, making it difficult to take time off work) and hence a desire for testing convenience and rapidly accessible results. Three quarters of the participants expressed preferences for rapid testing over the current standard-of-care and more than half preferred to be tested in non-healthcare settings.…”
Section: Discussionsupporting
confidence: 87%
“…A long history of discrimination and oppression means that many LGBTQ people are reluctant to be open about their sexuality or gender identity, despite positive changes in societal attitudes. Numerous studies demonstrate that many LGBTQ patients show a marked preference for LGBTQ or LGBTQ‐friendly health care providers. It therefore follows that LGBTQ health professionals have distinct information needs, either because of their patients’ or because of their own health information needs, an observation confirmed by Fikar & Keith's respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that mistrust, disclosure difficulties, and internalized homophobia may limit healthcare access and delay presentation for care among MSM. [11][12][13][14] A recent study of New York MSM found that although most had seen a clinical provider recently, 39 % did not disclose sexual activity with male partners, with lower rates among African American and Latino MSM. 15 Medical mistrust, [16][17][18][19] discrimination experiences, [18][19][20][21] conspiracy beliefs, 19,22,23 and concerns about disclosure may be particularly significant barriers to PrEP access among MSM of color, as demonstrated by a recent PrEP acceptability study among African American MSM.…”
mentioning
confidence: 99%